Value Proposition Design: Multi-sided Platform Business Model - Abdul, Jamaludin Ibrahim; Ahmad Dahlan, Abdul Rahman (MyHCI-UX C/O MYHCI-UX, UTM IBS, UiTM, 2021)
Discourse on Value Proposition Design for Multi-Sided platform business model in the context of Human Computer Interaction and User Experience (HCI-UX) is scarce. This paper proposes a consideration how HCI-UX could receive compelling benefits from the use of Value Proposition Design (VPD) concept. Understanding of the underpinning principles of VPD will shade new horizon for HCIUX. Designing the right value proposition for the targeted customer segment is vital to product and business success. Disruptive business models have been known to have compelling value propositions embedded in them. Value proposition can be designed using the value proposition canvas approach and embedded in the business model. It will undergo several innovations to get the best fit meeting the customer profile. However, the value proposition of multi-sided platform business model has an extra advantage. It is not only designed by having the right communities or customer segments onto a platform creating mutually beneficial values. In addition, it harnesses the network effects resulted from the value creation. This is the significant advantage it has over the traditional value proposition canvas design. The multiplier attribute of the network effects accelerate growth achieving faster business model fit. Network effects are the main reason that makes multisided platform business model predominant in unicorn companies, start-ups, and established businesses. Reframing value proposition problems from HCI-UX and other related fields of knowledge into multi-sided platform could help these areas take advantage of the network effects. This is especially true if the network effects can be made amenable to optimization.